Organoleptic Test of Breadfruit Nuggets - Priyanti, Diani Putri; Kartini, Luh Putu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the development of nuggets made from breadfruit as an innovation of local food products. Organoleptic tests were conducted to assess the quality of taste, aroma, color, and texture involving 25 panelists. The results showed that breadfruit nuggets had very good organoleptic quality with an average value of 86% for all variables tested. Breadfruit nuggets are considered to have great potential to be developed as a healthy food product with high economic value. This study opens up opportunities for diversification of breadfruit-based products and suggests further research related to nutritional analysis, product stability, and commercialization strategies.